Determining Optimum Point of Robusta Coffee Bean Roasting Process for Taste Consistency (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2018)
Roasting is an important coffee bean processing that affect quality and flavor consistency. Roasting parameters are summarized in the roasting profile which describe density, water content, pH, yield, taste, time and temperature as well as roasting technique of the beans. Roasting profile which is important for roaster master varies according to coffee bean types, such as Arabica and Robusta collected from specific area. Therefore, this paper studiedthe process of roasting Robusta coffee beans collected from Sumber Asin, Malang with normal roast technique using roaster machine in order to get taste consistency with determining optimum point from these parameters. During roasting process, temperature changes were recorded every two minutes for 20 minutes after temperature reached 180 OC. Density, moisture content, yield, pH, and flavor were assessed after roasting. The normal roasting technique required optimum roasting time of 9-10 minutes at 180 ± 5 OC, density value of 0.49 ± 0.04 gram/ml, water content of 3.5 ± 1.3%, losses 9.7 ± 1.9%, pH 5.3 ± 0.2, with chocolaty, spicy, and thick body flavors. There was strong correlation between Robusta roasting profile with all parameters measured. The optimal Robusta roasting time could be determined from intersec-tion  line between temperature and density in the roasting profile. Robusta optimum roasting time is about 10 minutes. The roaster master could use optimum roasting time in accordance to roasting quality.